Risk Stratification in Pediatric Acute Respiratory Distress Syndrome - Wong, Judith Ju-Ming; Phan, Huu Phuc; Phumeetham, Suwannee; Ong, Jacqueline Soo May; Chor, Yek Kee; Qian, Suyun; Samransamruajkit, Rujipat; Anantasit, Nattachai; Gan, Chin Seng; Xu, Feng; Sultana, Rehena; Loh, Tsee Foong; et al. (Lippincott, Williams & Wilkins, 2017)
Objectives: The Pediatric Acute Lung Injury Consensus Conference developed a pediatric specifiic defiinition for acute respiratory distress syndrome (PARDS). In this definition, severity of lung disease is stratified into mild, moderate, and severe groups. We aim to describe the epidemiology of patients with PARDS across Asia and evaluate whether the Pediatric Acute Lung Injury Consensus Conference risk stratification accurately predicts outcome in PARDS. Design: A multicenter, retrospective, descriptive cohort study. Setting: Ten multidisciplinary PICUs in Asia. Patients: All mechanically ventilated children meeting the Pediatric Acute Lung Injury Consensus Conference criteria for PARDS between 2009 and 2015. Interventions: None. Measurements and Main Results: Data on epidemiology, ventilation, adjunct therapies, and clinical outcomes were collected. Patients were followed for 100 days post diagnosis of PARDS. A total of 373 patients were included. There were 89 (23.9%), 149 (39.9%), and 135 (36.2%) patients with mild, moderate, and severe PARDS, respectively. The most common risk factor for PARDS was pneumonia/lower respiratory tract infection (309 [82.8%]). Higher category of severity of PARDS was associated with lower ventilator-free days (22 [17-25], 16 [0-23], 6 [0-19]; p < 0.001 for mild, moderate, and severe, respectively) and PICU free days (19 [11-24], 15 [0-22], 5 [0-20]; p < 0.001 for mild, moderate, and severe, respectively). Overall PICU mortality for PARDS was 113 of 373 (30.3%), and 100-day mortality was 126 of 317 (39.7%). After adjusting for site, presence of comorbidities and severity of illness in the multivariate Cox proportional hazard regression model, patients with moderate (hazard ratio, 1.88 [95% CI, 1.03-3.45]; p = 0.039) and severe PARDS (hazard ratio, 3.18 [95% CI, 1.68, 6.02]; p < 0.001) had higher risk of mortality compared with those with mild PARDS. Conclusions: Mortality from PARDS is high in Asia. The Pediatric Acute Lung Injury Consensus Conference defnition of PARDS is a useful tool for risk stratification.